Impact of Sanatorium Treatment on the Quality of Life of Patients with Lumbosacral Spine Pain Syndrome - Lech Grzelak; Agnieszka Kikosicka; Agnieszka Szajerska; Mateusz Szostak (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Lumbosacral spine pain increasingly impacts the quality of life for many individuals, affecting both physical and social aspects. Addressing this issue through effective prevention and treatment is crucial to mitigating its negative effects on society, especially in developed countries.